The influence of 5-fluorouracil on activity of thymidine phosphorylase in gastric adenocarcinoma and normal adjacent tissue - Stashkevych, M.; Khomutov, E.; Dumanskiy, Y.; Matviyenko, A.; Zinkovych, I. (Experimental Oncology, 2014)
The aim of the present study was to evaluate the change of thymidine phosphorylase (TP) activity in gastric adenocarcinoma and adjacent tissue upon the intraarterial administration of 5-fluorouracil (5-FU). Matherials and methods: The specimens of tumor and adjacent tissue were obtained by surgical operation on 36 patients (20 men and 16 women aged from 38 to 82 years) with gastric adenocarcinoma (stages II–IV). 5-FU was administered in the bolus dose to the gastroepiploic artery 2–60 min before the tumor resection. The concentration of 5-FU and activity of TP in both tissues were determined by high performance liquid chromatography method. Results: The concentration of 5-FU was decreased in a time-dependent manner in both tissues, though the interpatient variability of this value was much less in tumor tissue. The activity of TP was decreased with the course of the time after 5-FU administration in tumor and normal adjacent tissue. There were statistically significant differences in the TP activity in both tissues between 2–20 min and 40–60 min after 5-FU injection (p < 0.05). Conclusion: 5-FU administration results in the decrease of TP activity in tumor and normal adjacent tissues that might have importance for chemotherapy with fluoropyrimidines. Key Words: 5-fluorouracil, thymidine phosphorylase, gastric adenocarcinoma, normal mucosa.